Surgical Outcome of Low-Grade Glioma in Non-Eloquent Cortex - Asghar Ali, Waheed Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Aim and objective: To identify the surgical outcomes of low-grade gliomas in the non-eloquent cortex. Materials and method: The prospective study was conducted at the neurosurgery department of Lady Reading Hospital Peshawar from July 2019 to June 2022 after approval from the institutional review board. A total of 58 participants were included in the study through a convenient sampling technique. The age of the participants was from 15-60 years, including both males and females. Pre- and post-Karnofsky performance score (KPS) was calculated, Moreover, overall survival (OS) and progression-free survival (PFS) were calculated. All the data was collected from patients’ assessments and histopathological lab reports and were analyzed by using the latest version of SPSS 24. Results: A total of 58 patients were selected in the current study ranging from 15 to 60 years. 25.86 % were from 31-40 years of age and 32.75 % of them were from 41-50 years of age. 56.89 % of them were males and 43.10 % were female participants. Pre-operative KPS scores were 100-90 % (46.55 %), 80-70 % (32.75 %), and 60-50 % (20.68 %). 64.79 % had a headache and 1.03 % of them had seizures. 29.31 % had total removal, 37.93 % had GTR, 20.68 % had STR, and 12.06 % of the individual’s biopsies were taken. The post-op KPS scores were 100-90 % (70.68 %), 80-70 % (18.98 %), and 60-50 % (10.34 %). Overall PFS was 75.86 %, while the OS was 81.03 %. Conclusion: The current concluded that the careful surgical selection for non-low-grade gliomas in the non-eloquent cortex was the safe intervention and can result in favorable outcomes like enhanced KPS, PFS, and OS scores after the surgery. Keywords: Karnofsky performance score, Progression-free survival, overall survival, GTR, STR